On the Marriageability of Men. Issue 1 (January 2016) - Bridges, Tristan; Boyd, Melody L.
Abstract: The "marriageability of men" is an argument used in sociological research to understand demographic changes in marriage and to analyze social dynamics associated with gender, race, class, family, the workplace, incarceration, and more. While some are marrying later and others are foregoing marriage altogether, a lack of marriageable men is often part of the argument concerning new patterns of family formation in the United States. Research mobilizing the marriageability of men hypothesis spans a great deal of subfields of sociological research, not all in conversation with one another – and not all explicitly making use of the term. This article collects these diverse strands of thought and presents an argument for how and why men are less marriageable, what this means, and why it means different things for different groups of men and women. Racialized and classed conceptions of masculinity create different kinds of struggles for different groups of men and work against their marriageability for different reasons. We discuss the impact of incarceration, new struggles in a service economy, and shifts in women's perceptions and expectations of what qualifies men as "marriageable."